(untitled) (Revista Contexto & Saúde, 2026)
The objective was to analyze the reorganization of Primary Care health actions and services during the COVID-19 pandemic in two small municipalities in Bahia. This is qualitative and descriptive research that utilized 15 semi-structured interviews with managers and health workers from two Family Health Strategy (FHS) units in the municipalities of Souto Soares and Iraquara (BA), as well as documentary analysis. Data were analyzed with the support of MAXQDA software for Content Analysis and the categorization of health actions and services. Results evidenced changes in operational flows and the work process; monitoring of COVID-19 cases; strengthening of intersectorality; creation of specific spaces; protocol development; and general actions such as guidance to the population, sanitary barriers, and testing. Furthermore, the study highlighted the use of technologies, messaging apps, and permanent education. It is concluded that the reorganization of Primary Health Care (PHC) is an imperative necessity for the development of more qualified, humane, and resolute healthcare.